The essence and features of housing legal relations - M. Ye. Vasylenko (Bulletin of Kharkiv National University of Internal Affairs)
The analysis of scientific viewpoints of scholars on the interpretation of the concepts of “social relations”, “legal relations” and “housing legal relations” has been carried out, and the author's own definition for the latter has been proposed. It has been established that legal relations are bilateral volitional relations between subjects of law which arise on the basis of legal provisions and are regulated by them with a view to recognising, exercising and protecting their rights, freedoms and interests. A key characteristic for legal relations is their voluntary nature and purpose, as they arise exclusively for a specific purpose. The specificity of legal relations depends on the sphere of public life in which they arise and the rules of which branch of law they are regulated.